2009
DOI: 10.1590/s0100-736x2009000500001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Escherichia coli isolated from bovine mastitic milk

Abstract: RESUMO.-[Análise de Escherichia coli isolada de leite de vacas com mastite.]A um longo tempo a mastite tem sido reconhecida como a doença que provoca as maiores perdas econômicas nos rebanhos leiteiros. De fevereiro a novembro de 2004, foram coletadas 670 amostras de leite mastítico de vacas, provenientes de dois estados brasileiros, das quais foram isoladas 231 cepas de Escherichia coli. Estas cepas foram analisadas para a detecção dos genes de produção de Shiga toxina (stx 1 e stx 2) e do gene da intimina (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
4
17
3
Order By: Relevance
“…Heterogeneous profiles of antimicrobial resistance were also described by Rangel and Marin (2009) and Solomakos et al (2009) …”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous profiles of antimicrobial resistance were also described by Rangel and Marin (2009) and Solomakos et al (2009) …”
Section: Discussionmentioning
confidence: 99%
“…Mastitis is an important and a persistent infection producing high economies losses due to poor milk quality, reduced milk yield and increased expenditure on treatment especially staphylococcal mastitis [16] which resembled 63.37% through the current study and bacteriological examination shows that S. aureus was the main causative agent of clinical mastitis in cows [34 [17]; [18]; [19] , respectively. However, the findings [71.4%] of S. aureus by [20] are much higher than the present report.…”
Section: Discussionmentioning
confidence: 86%
“…Slime synthesis is controlled by the ica [intercellular adhesion] operon. Coexpression of icaA with icaD leads to a significant increase in activity and is related to phenotypic expression of the capsular polysaccharide [34] . In this study, slime factor production of MRSA isolates were detected by PCR targeting icaA and icaD genes and found that 5 [4] .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, stx1, stx2, and intimin genes were evaluated. In the previous studies, researchers also stated variations in the presence rates for these genes [5,20,21,22]. Although, Momtaz et al (2012) and Kobori et al (2004) stated a higher presence rate, other researchers [18,23,24] could not detect the gene in E. coli strains.…”
Section: Discussionmentioning
confidence: 98%
“…E. coli is an environmental mastitis pathogen, which causes clinical signs in mammary glands in cows and its resistance against antibiotics depends on herd management. In previous studies, various antibiotic resistance profi les and rates in E. coli strains were stated in previous studies especially for oxytetracycline [29,30,31,32], penicillin [22,32,33,34], macrolides [21,35,36], trimethoprimsulphamethoxazole [6,36,37], fl uoroquinolones [35,36] and cephalosporins [38]. In the presented papers, resistance profi les of E. coli strains were evaluated for vancomycine, danofl oxacin, oxytetracyline, enrofl oxacin, amoxicillin-clavulanic acid, trimethoprim-sulphamethoxazole, ampicillin and tetracycline.…”
Section: Discussionmentioning
confidence: 99%